Community Empowerment Strategy through Competitive Creative Economic Development for the Improvement of Family Income - Sarwani, Sarwani; Rahman, Erni (PINISI Discretion Review, 2023)
The aim of the research is to analyze community empowerment strategies through developing a competitive creative economy in an effort to increase family income at UKM Shaza Depok. The method used in this research is a qualitative research method. The unit of analysis in this research is the source who is the informant, namely the owner of UKM Shaza Depok, the Management Department of UKM Shaza Depok and employees who work at UKM Shaza Depok. Data collection techniques in this study: interviews, observation, FGD (Focus Group Discussion) techniques, documentation. Data analysis uses 2 kinds of methods, namely SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) and Balanced Scorecard. The results of the research show that the community empowerment strategy. From several results from the Balance Scorecard (BSC) perspective, what Shaza Depok UKM needs is: (1) Strengthening village communities as subjects of empowerment development, (2) Improving the welfare of village communities, (3) Increasing village community satisfaction with Shaza Depok UKM services, ( 4) Optimizing competitiveness in an effort to increase income, (5) Increasing community participation in developing product innovation and improving more creative marketing, (6) Improving product and service quality, (7) Increasing employee work motivation, (8) Increasing competency employees, and (9) Improving product information technology and systems.